Socio-Economic Impact of Cashew Cultivation in Cuddalore District of Tamil Nadu-An Overview (Indian Journal of Extension Education, 2010)
Tamil Nadu is one of the important cashew growing states in East Coast region of the country. Cuddalore district of the state has second largest area under cashew and second highest number of cashew processing industries which contributes a major share in the cashew economy. This study was conducted to assess the socio-economic impact of cashew cultivation in this district, with cashew growers having cashew gardens of seedling (32) and graft origin (33). It was found that cashew cultivation was the main source of income for livelihood of the respondents. The knowledge and adoption scores of farmers with graft cashew gardens were significantly higher than that of the other category whereas there was no significant difference between the perception level of both the categories. The average technology gap score of the farmers with seedling gardens was significantly higher than that of the other category. However, the use of cashew grafts, as planting material for cashew gardens did not give any significant contribution to the yield. It was suggested based on the correlation studies that by imparting training to the cashew growers on improved cashew cultivation practices, the knowledge level of the higher than that of the other category. However, the use of cashew grafts, as planting material for cashew gardens did not give any significant contribution to the yield. It was suggested based on the correlation studies that by imparting training to the cashew growers on improved cashew cultivation practices, the knowledge level of the respondents could be improved and in turn adoption, perception levels whereas adoption and technology gaps of the respondents could be narrowed down. The Department of Horticulture, Government of Tamil Nadu needs to take up intensive efforts to educate the cashew growers on improved cashew cultivation practices.